طريقة العصف الذهني ودورها في تنمية مهارات التعبير الكتابي لدى طلبة الصف العاشر بالمدارس الخاصة في سلطنة عمان - Ahmed Al-Husaini, A.A.; Rosni Samah (Universiti Sains Islam Malaysia, 2024)
This experimental study aimed to diagnose the effectiveness of brainstorming teaching method on the tenth-grade students writing skills, and its impact on the development of creative writing. Community of the study the Silver Jubilee Private School and Mazen Bin Gharouba Private School. The study sample were (60) students, divided into two groups, a control group and the experimental group. Study tools included: The written test for the tenth-grade students, and the teacher's guide to teaching written expression using the method of brainstorming. The study findings revealed that; the teaching of written expression using the brainstorming method was effective in the development of creative written expression skills among the tenth-grade students. The students of the experimental group surpassed the students of the control group in the post-test of creative written expression skills.